2001
DOI: 10.1542/peds.108.6.e97
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Hospitalization Trends in Charleston, South Carolina, 1956 to 1997: Twenty-fold Increase Among Black Children During a 30-Year Period

Abstract: ABSTRACT. Objective. The increase in asthma prevalence has been documented worldwide, affecting many races living in many different climates. Multiple studies have demonstrated that the most striking prevalence and morbidity of asthma in the United States has been in black children, but little research has determined the scale of the increase, or specifically when the disease became severe in this group. This study sought to determine exactly when the rise in asthma hospitalizations among black patients began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…A study from Charleston, South Carolina, showed that over the interval from 1956 through 1997, African Americans experienced a 20-fold increase in the rate of hospital discharge for asthma compared with a 5-fold increase for whites. 85 In another large multicenter study of ED visits by adults, asthma management did not vary by race in the ED; however, blacks and Hispanics were twice as likely to be hospitalized for their asthma episode and to experience symptoms 2 weeks after hospital discharge. 86 These findings suggest either that the asthma episodes are more severe in African Americans and Hispanics by the time they arrive in the ED or that their asthma is less responsive to treatment.…”
Section: Tertiary Prevention: Mitigating Disease Complicationsmentioning
confidence: 95%
“…A study from Charleston, South Carolina, showed that over the interval from 1956 through 1997, African Americans experienced a 20-fold increase in the rate of hospital discharge for asthma compared with a 5-fold increase for whites. 85 In another large multicenter study of ED visits by adults, asthma management did not vary by race in the ED; however, blacks and Hispanics were twice as likely to be hospitalized for their asthma episode and to experience symptoms 2 weeks after hospital discharge. 86 These findings suggest either that the asthma episodes are more severe in African Americans and Hispanics by the time they arrive in the ED or that their asthma is less responsive to treatment.…”
Section: Tertiary Prevention: Mitigating Disease Complicationsmentioning
confidence: 95%
“…A large study of 12,388 children from 89 centres across the USA found that the risk of asthma was 1.64 times as great in African-American children as in the rest of the population [39]. The higher rate of asthma in AfricanAmerican children has not always been present, as a recent study has shown that asthma hospitalisations increased 20-fold in African-Americans between 1960 and 1990, but only fivefold in European-Americans [40]. Other investigations examining populations migrating from their tropical origins to a more developed society have revealed similar patterns.…”
Section: What Are the Consequences Of These Differences In Pro-th2 Almentioning
confidence: 99%
“…Smoking among minorities, especially African Americans, has increased more rapidly than among whites, and the prevalence of COPD in the former has risen accordingly. 3 Data collected by the Centers for Disease Control and Prevention, National Center for Health Statistics, [5][6][7][8][9] show that racial and ethnic differences in asthma prevalence, health-care utilization, and mortality exist; however, few studies 3 have addressed racial disparities in COPD care. Our previous work 10 has shown that medical resource utilization varies between COPD and asthma patients.…”
mentioning
confidence: 99%